2014
DOI: 10.1158/0008-5472.can-13-2479
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a Impairs Homologous Recombination–Mediated DNA Repair in Human Papillomavirus–Positive Head and Neck Tumors

Abstract: The p16INK4a protein is a principal cyclin-dependent kinase inhibitor that decelerates the cell cycle. Abnormally high levels of p16INK4a are commonly observed in human papillomavirus (HPV)-positive head and neck squamous cell carcinomas (HNSCC). We and others found that p16INK4a overexpression is associated with improved therapy response and survival of patients with HNSCC treated with radiotherapy. However, the functional role of p16INK4a in HNSCC remains unexplored. Our results implicate p16INK4a in regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 51 publications
12
108
0
1
Order By: Relevance
“…Hence, additional factors are likely to be involved. One possible mechanism could be the inhibition of homologous recombination, though, UPCI-SCC-154 cells are reportedly deficient for HR due to the high expression of p16 and/ or lack of expression of BRCA2 [23,24]. Further studies are necessary to identify additional factors contributing to radiosensitization and to identify predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, additional factors are likely to be involved. One possible mechanism could be the inhibition of homologous recombination, though, UPCI-SCC-154 cells are reportedly deficient for HR due to the high expression of p16 and/ or lack of expression of BRCA2 [23,24]. Further studies are necessary to identify additional factors contributing to radiosensitization and to identify predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason it has been included as prognostic factor in the MVA, by extending to the new population the results reported by Calais et al (1998). In this regard, emerging evidence supports HPV association with better response and survival in HNSCC patients treated with RT (Dok et al, 2014), suggesting the intriguing role of p16INK4a status as an independent predictive marker. However, the mechanism triggering this biological effect still has to be fully understood and it is not taken into account in our model.…”
Section: Discussionmentioning
confidence: 91%
“…the study also showed a trend towards improved treatment outcome for patients with HPV positive tumors. In the analysis of association of tumor p16INK4A expression with therapeutic response in a prospectively collected cohort of patients with HNSCC treated with radiotherapy alone, showed that tumor cell expression of p16INK4A in this group of patients is associated with markedly improved treatment response and survival and that p16INK4A expression status is an independent prognostic factor for both outcomes 14 .…”
Section: Detection Of Hpv Infection-mentioning
confidence: 99%